Evaluation of Vertical Alignment on Copper Smelter Access Road PT Wanhong Nonferrous Recycling Utilization - Sulawesi - Sih Noormantoro Dwi Pandumukti; Indrastuti Indrastuti (Fakultas Teknik Sipil dan Perencanaan, 2023)
This research paper, based on the Indonesian Standard geometric road guidelines, evaluates the vertical alignment of the access road to PT Wanhong Nonferrous Recycling Utilization in the Palu Special Economic Zone. The objective was to assess the feasibility of the existing road geometry and ensure compliance with safety and comfort standards. The study found that the road falls under the JKC category and is classified as mountainous terrain, with a maximum incline of 12%, while the actual incline measures are 9.37%. The speed plan of the road adheres to the minimum velocity requirement for JKC classification. The study utilized surveying equipment, Google Earth, and AutoCAD Civil 3DÂ®. The findings emphasize the importance of proper road geometry in ensuring safe and efficient transportation infrastructure, particularly in industrial areas.